Greek and Roman mythology A to Z - Daly, Kathleen N.; Rengel, Marian (New York Facts On File, 2004)
Alphabetically listed entries identify and explain the characters, events, important places, and other aspects of Greek and Roman mythology
Originally published: c1992, in series: Daly, Kathleen N. Mythology A to Z
Includes bibliographical references (p. 138-139) and index
Keywords: Mythology, Classical -- Encyclopedias, Juvenile